Nitric Oxide Responsive Heavy Metal-Associated Gene AtHMAD1 Contributes to Development and Disease Resistance in Arabidopsis thaliana - Imran, Q. Muhammad; Falak, Noreen; Hussain, Adil; Mun, Bong-Gyu; Sharma, Arti; Lee, Sang-Uk; Kim, Kyung-Min; Yun, Byung-Wook (Frontiers in Plant Science, 2016)
Exposure of plants to different biotic and abiotic stress condition instigates significant change in the cellular redox status; resulting in the elevation of reactive nitrogen species that play signaling role in mediating defense responses. Heavy metal associated (HMA) domain containing genes are required for spatio-temporal transportation of metal ions that bind with various enzymes and co-factors within the cell. To uncover the underlying mechanisms mediated by AtHMA genes, we identified 14 Arabidopsis HMA genes that were differentially expressed in response to nitrosative stress through RNA-seq analysis. Of those 14 genes, the expression of eight HMA genes was significantly increased, whereas that of six genes was significantly reduced. We further validated the RNA-seq results through quantitative real-time PCR analysis. Gene ontology analysis revealed the involvement of these genes in biological processes such as hemostasis and transport. The majority of these nitric oxide (NO)-responsive AtHMA gene products are carrier/transport proteins. AtHMAD1 (At1g51090) showed the highest fold change to S-nitrosocystein. We therefore, further investigated its role in oxidative and nitrosative mediated stress conditions and found that AtHMAD1 has antagonistic role in shoot and root growth. Characterization of AtHMAD1 through functional genomics showed that the knock out mutant athmad1 plants were resistant to virulent Pseudomonas syringae (DC3000) and showed early induction and high transcript accumulation of pathogenesis related gene. Furthermore, inoculation of athamd1 with avirulent strain of the same bacteria showed negative regulation of R-gene mediated resistance. These results were supported by hypersensitive cell death response and cell death induced electrolyte leakage. AtHMAD1 was also observed to negatively regulate systemic acquired resistance SAR as the KO mutant showed induction of SAR marker genes. Overall, these results imply that NO-responsive AtHMA domain containing genes may play an important role in plant development and immunity.